Association Between Deliberate Self-Harm and Coping in Adolescents: A Critical Review of the Last 10 Years' Literature - Guerreiro, Diogo F.; Cruz, Diana; Frasquilho, Diana; Santos, José C.; Figueira, Maria L.; Sampaio, Daniel (Archives of suicide research, 2013)
Coping is commonly associated with deliberate self-harm (DSH) in adolescents. This article reviews the published literature from 2000 to 2010, aiming to highlight the current evidence supporting this association. Eighteen studies met the inclusion criteria, a total sample of 24,702 subjects was obtained and 17% were DSH cases. Emotion-focused coping style and in particular avoidant coping strategies have consistently been associated with DSH in adolescents. Problem-focused coping style seems to have a negative relation. Most studies were cross-sectional, which seriously limits our conclusions on causality. There is a clear need for more systematic studies, performed in accordance with consensual methodology.